PETA KEKERASAN DALAM RUMAH TANGGA (Studi Atas Perkara Perceraian di Pengadilan Agama Batang - Widyastuti (MUWAZAH : jurnal kajian gender, 2016)
This paper is the result of research that maps of domestic violence in divorce cases in Batang Religious Court by 2015. This literature research used a qualitative approach. Secondary data sources such as the archives of the Religious Court divorce case Batang 2015 and; other data that support the research. Data collection techniques using documentation and interviews. Analysis techniques using interactive analysis model. The results showed that, the map of domestic violence in divorce cases in Batang Religious Court in 2015, among others: physical violence, which in divorce case referred to, physical cruelty and mental cruelty, as many as 32 cases; psychological violence, as many as 628 cases; sexual violence, no and; economic violence (penelantara households), as many as 1036 cases.